2011
DOI: 10.1017/s0950268811000641
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of methicillin-resistantStaphylococcus aureuscolonization in residents in community long-term-care facilities in Spain

Abstract: SUMMARYMethicillin-resistant Staphylococcus aureus (MRSA) is highly prevalent in Spanish hospitals and community long-term-care facilities (LTCFs). This longitudinal study was performed in community LTCFs to determine whether MRSA colonization is associated with MRSA infections and overall mortality. Nasal and decubitus ulcer cultures were performed every 6 months for an 18-month period on 178 MRSA-colonized residents (86 490 patient-days) and 196 non-MRSA carriers (97 470 patient-days). Fourteen residents dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 35 publications
(62 reference statements)
1
2
0
Order By: Relevance
“…Regarding MSSA, our results are consistent with studies conducted in inpatient and nursing home participants that also failed to find an association ( 4 7 ). Many of these studies were underpowered, calling for larger scale investigations.…”
Section: Discussionsupporting
confidence: 91%
“…Regarding MSSA, our results are consistent with studies conducted in inpatient and nursing home participants that also failed to find an association ( 4 7 ). Many of these studies were underpowered, calling for larger scale investigations.…”
Section: Discussionsupporting
confidence: 91%
“…Muder et al showed that 25% of rehabilitation and long-term-care residents colonized with MRSA developed MRSA infections compared to 4% of those not colonized with MRSA [55]. Despite some earlier literature linking MDR infections to an increase in mortality in at least certain scenarios and in the short term [60, 61], the majority of observations failed to show significant changes in long term all-cause mortality [62]; in a study focusing on colonization by MRSA and ESBL-producing GNB, colonization did not increase mortality or morbidity as assessed after 12 months [63]. Lee et al used a mathematical model to predict that use of contact precautions for all MRSA carriers would reduce prevalence of MRSA, but they did not anticipate changes in clinical outcome [64].…”
Section: Public Health Importance and The Prognostic Role Of Colonizamentioning
confidence: 99%
“…MRSA-related infection has been debated for some time now and some authors believe it is very important to diagnose MRSArelated infection or colonisation for preventing further spread of MRSA [11][12][13]. MRSA-related infections tend to be more severe or even fatal [14].…”
Section: Discussionmentioning
confidence: 99%